Blip SOS: acessório IoT para envio de SOS com geolocalização em situações emergenciais - Silva, Caroline Rosa da (2022)
There are several risk situations where someone may find themselves in need of asking for help, like a suspicious taxi ride, a kidnapping or even an accident. Usually the most viable way of seeking for help is the cellphone, but this could easily become unable due to no internet reception or even an inability of accessing the device in order to send messages or make calls. Thinking about that, this project proposes the idea of a product and the development of its project, which consists in an IoT (Internet of Things) device, ideally a small accessory that could be always kept close by the user, in which the simple act of pressing a button triggers the sending of a message containing its geolocation and a request for help. The communication happens through a LoRaWAN (LoRa Wide Area Network), which works regardless the availability of a cellphone, and is able to bypass the SOS message to an Amazon Web Services (AWS) cloud server, which sends it to a list of contacts (previously selected through a mobile app) via WhatsApp and SMS (Short Message Service). Thereby, the people selected by the user will be able to know that the user is in danger and where they are located.